ASPECTS OF SEEDLING PRODUCTION OF Clathrotropis brunnea Amshoff, A THREATENED LEGUME TREE FROM COLOMBIAN RAINFORESTS - Daibes, Luis Felipe; Prato, Andrés Iván; Carvalho, Fabricio Eulalio Leita (Floresta, 2023)
Seedling production is crucial to assist restoration and conservation practices of tropical rainforest species. In the present study, we evaluated seedling production of Clathrotropis brunnea Amshoff, a legume tree native to tropical forests of Colombia. Seedling emergence parameters were assessed regarding two classes of seed mass (small seeds < 6.0 g and large seeds > 6.1 g) and tree levels of seed moisture content (control, 30% and 25%). Initial growth was evaluated in two sizes of plastic bags (small: 10 cm diameter x 25 cm height, with a volume of 1,700 cm3, and large: 15 cm x 35 cm and volume of 3,900 cm3), besides tree growth periods in the nursery (170, 205 and 235 days after sowing – DAS). Large seeds provided higher seedlings and reached a greater emergence percentage (93%) compared to the small ones (79%). On average, seeds reached 73% of emergence in the three moisture levels, including when desiccated from 47% in the control (fresh seeds) to 25%. To optimize seedling production and costs, large seeds can be sown in small bags, growing for a minimum of 205 DAS. The in-field performance of the produced seedlings remains to be tested according to these recommendations.